Changes in Medicare Physician Reimbursement for Stroke Procedures from 2000 to 2019. Issue 1 (25th February 2021) - Pines, Andrew R; Haglin, Jack M; Demaerschalk, Bart M
ABSTRACT: BACKGROUND: There is limited data regarding financial trends for procedural reimbursement in stroke care. A comprehensive understanding of such trends is important as continued progress is made to advance agreeable reimbursement models in the care of stroke patients. OBJECTIVE: To evaluate monetary trends in Medicare reimbursement rates for commonly utilized procedures in stroke care from 2000 to 2019. METHODS: The Centers for Medicare & Medicaid Services was queried for the included Current Procedural Terminology (CPT) codes and reimbursement data were extracted. The CPT codes compiled were the most commonly performed procedures for stroke-related International Classification of Diseases (ICD)-10 codes at our institution (I60-I63). Additionally, data were collected for alteplase and telestroke codes. The rate of change between procedures was compared utilizing an unpaired Student's t -test. All monetary data were adjusted for inflation to 2019 US dollars utilizing the US Consumer Price Index. RESULTS: After adjusting for inflation, the average reimbursement for stroke (ICD I60-I63) procedures decreased by 11.2% from 2000 to 2019 (average of −0.43% per year). The adjusted reimbursement rate for included telestroke codes decreased by 12.1% from 2010 to 2019 (average of −1.4% per year). From 2005 to 2019, the reimbursement for alteplase rose by 163.98% (average of +7.3% per year). CONCLUSION: When adjusted for inflation, Medicare reimbursement for common stroke procedures has decreased from 2000 to 2019. In contrast, reimbursement for alteplase has increased markedly. It is important to be aware of these trends in order to contextualize healthcare economic analyses and inform discussions.